(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article explores the vital intersection of commerce, management, political science, and nutritional sciences in addressing global challenges related to food security and economic resilience. Through a comprehensive analysis, it uncovers synergies among these disciplines, emphasizing collaborative strategies for sustainable solutions. Drawing from successful case studies, the article proposes integrated frameworks and policy recommendations to transcend borders and build a resilient future